2009
DOI: 10.1021/bi901005f
|View full text |Cite
|
Sign up to set email alerts
|

Structural Polymorphism and Multifunctionality of Myelin Basic Protein

Abstract: Central nervous system myelin is a dynamic entity arising from membrane processes extended from oligodendrocytes, which form a tightly wrapped multilamellar structure around neurons enabling rapid and efficient signal propagation. The gene of oligodendrocyte lineage (golli) gives rise to a variety of developmentally regulated splice isoforms of myelin basic protein (MBP), denoted golli for early forms and classic for later ones. In mature myelin, the predominant splice isoform of classic MBP is 18.5 kDa; its c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
246
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 192 publications
(250 citation statements)
references
References 87 publications
3
246
0
1
Order By: Relevance
“…important CNS protein, myelin basic protein (MBP), that becomes helical at the myelin membrane surface (reviewed in ref. 16). Given that protein biological activity most often requires a folded, stable structure, we hypothesize that Nogo-66 adopts a defined structure when bound to the Nogo receptor in activity assays.…”
Section: Resultsmentioning
confidence: 99%
“…important CNS protein, myelin basic protein (MBP), that becomes helical at the myelin membrane surface (reviewed in ref. 16). Given that protein biological activity most often requires a folded, stable structure, we hypothesize that Nogo-66 adopts a defined structure when bound to the Nogo receptor in activity assays.…”
Section: Resultsmentioning
confidence: 99%
“…Alternatively, they may result from reduced MBP levels in response to increased sncRNA715 levels. The importance of MBP for the elaboration of the distinct molecular composition of the oligodendroglial membrane (and myelin) has been demonstrated in detail previously [6] and MBP is associated with the actin and tubulin cytoskeleton [4]. It remains to be shown if sncRNA715 targets the synthesis pathway of other proteins in addition to MBP, which may also lead to the observed effects on cellular morphology and induction of apoptosis.…”
Section: Sncrna715 Affects Morphology and Cell Numbersmentioning
confidence: 96%
“…MBP acts as an intermembrane adhesion protein between the cytoplasmic leaflets of the myelin sheath. The predominant size and charge isoform of MBP in healthy and mature myelin has a molecular weight of 18.5 kDa and a net positive charge of 19 (12,13). Several studies conducted with model and extracted myelin bilayers (9,(14)(15)(16)(17)(18)(19) showed that because of its high content of positively charged residues, MBP binds to the negatively charged lipids of the cytoplasmic leaflets of the bilayer via electrostatic interaction in addition to hydrophobic interactions.…”
mentioning
confidence: 99%